Basic English for Fifth Grade Students of Elementary School No. 2 Pengiangan, in Susut District, and in Bangli Regency - Dewa Made Agustawan; Reni Anggraeni; Nicholas Ferdeta Lakusa; I Gede Gunadi Putra; Ida Ayu Gede Sasrani Widyastuti (Outline Journal of Community Development, 2026)
This community service activity aims to improve the basic English skills of fifth-grade students at Pengiangan 2 Public Elementary School through interactive and fun training. The training focused on mastering basic vocabulary, simple expressions in everyday communication, and listening and speaking skills. The methods used included short lectures, educational games, dialogue practice, and group activities that encouraged active student participation. This activity involved fifth-grade students as the main participants with direct guidance from the implementation team. The results showed an increase in students' understanding of basic English vocabulary and increased confidence in pronouncing and using simple expressions. In addition, the interactive learning atmosphere was able to increase students' motivation to learn English. Thus, this basic English training made a positive contribution in supporting the development of foreign language competencies in elementary school students as provisions for facing future educational challenges.